PERBEDAAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIK ANTAR SISWA YANG MENDAPATKAN PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DAN JIGSAW - Dede Miftahul Mubarok; Nanang Nanang (Mosharafa: Jurnal Pendidikan Matematika, 2013)
Abstract:The Purpose of research is to know the differences of ability problem-solving mathematics between students who get Problem Based learning (PBL) with Jigsaw and for know respons students the model of learning who give. The results this  research  indicate: Not differences of ability problem solving mathematics between students who get Problem Based learning (PBL) learning with the students who get jigsaw learnin. Response the students between experiment class 1 who get learning of model Problem Based learning (PBL) with the students who get learning of model jigsaw, Response the students show positive response although sometimes there students who show negative response.